Comparison of foeto-maternal outcomes of planned verses emergency caesarean section - Mohite, Shravani; Anurag, Aakriti; Narshetty, Jayshree; Kumar, Sushil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Caesarean section is the most commonly performed obstetrical procedure. Caesarean sections can be divided into either planned or emergent, with the latter accounting for a higher frequency of complications. Methods: A prospective observational comparative study conducted in the department of obstetrics & gynaecology at MGM Medical College, Navi Mumbai over a period of 1 year. All women with singleton pregnancies undergoing emergency or elective caesarean section were included in the study. 600 patients were included with 300 in each group. Incidences of the various indications for caesarean sections was assessed for both groups. Relevant pre-operative, intra-operative and post-operative findings were noted. Maternal outcome assessed in terms of intraoperative complications, postoperative complications, need for intensive care unit (ICU) stay, maternal mortality rate. Foetal outcome was assessed in terms of APGAR score at birth, birth injuries, admission to neonatal intensive care unit (NICU), and perinatal mortality. Results: In our study, cases undergoing emergency caesarean sections were seen to have significantly higher rate of maternal as well as foetal complications as compared to those undergoing planned caesarean sections. Conclusions: Early pregnancy registration and thereby screening high risk patients for managing and planning accordingly for caesarean section, can significantly reduce the incidence of presumed risks, consequences and complications that may result due to emergency caesarean sections.